Prevention methods to reduce flood effects in government hospitals - Yusoff, Noor Ain; Shafii, Haryati; Omar, Roshartini; Buyung, Mohd Reduan (Akademia Baru, 2018)
The floods have a significant impact on hospital services. The floods in Kelantan for example, has resulted in the daily operation of the hospital were badly affected by the water entering and lack of other facilities. Thus, the study to ensure that the best prevention methods are needed to reduce the impact of flooding in government hospitals. In this study, the best method of prevention is seen through non-structural methods. Non-structural methods do not involve physical construction, but focus on knowledge, attitudes and practices to minimize risks and effects, particularly through increased public awareness, training and education. Measurement of knowledge, attitude and practice level of respondents in the face of flood disaster risk is using transportation and communication elements. 172 respondents among the hospital support management involved in managing patients during the floods have answered a questionnaire (quantitative) which was distributed to three hospitals in Kelantan state. The findings of this study found that knowledge of Amateur Radio and sign T should be given to the hospital support staff. In addition, communication training and the use of nicknames call sign should be enhanced among support staff in preparation for flooding in the future. The disclosure and training have to be done to reduce the risk of flood disaster at government hospitals.